Prenatal maternal stress and offspring aggressive behavior: Intergenerational and transgenerational inheritance - Mbiydzenyuy, Ngala Elvis; Hemmings, Sian Megan Joanna; Qulu, Lihle (Frontiers in Behavioral Neuroscience, 2022)
Even though studies have shown that prenatal maternal stress is associated with increased reactivity of the HPA axis, the association between prenatal maternal stress and fetal glucocorticoid exposure is complex and most likely dependent on unidentified and poorly understood variables including nature and timing of prenatal insults. The precise mechanisms in which prenatal maternal stress influence neuroendocrine signaling between the maternal-placental-fetal interface are still unclear. The aim of this review article is to bring comprehensive basic concepts about prenatal maternal stress and mechanisms of transmission of maternal stress to the fetus. This review covers recent studies showing associations between maternal stress and alterations in offspring aggressive behavior, as well as the possible pathways for the ‘transmission’ of maternal stress to the fetus: (1) maternal-fetal HPA axis dysregulation; (2) intrauterine environment disruption due to variations in uterine artery flow; (3) epigenetic modifications of genes implicated in aggressive behavior. Here, we present evidence for the phenomenon of intergenerational and transgenerational transmission, to better understand the mechanism(s) of transmission from parent to offspring. We discuss studies showing associations between maternal stress and alterations in offspring taking note of neuroendocrine, brain architecture and epigenetic changes that may suggest risk for aggressive behavior. We highlight animal and human studies that focus on intergenerational transmission following exposure to stress from a biological mechanistic point of view, and maternal stress-induced epigenetic modifications that have potential to impact on aggressive behavior in later generations.